STUDI META-ANALISIS TENTANG HUBUNGAN VENTILASI, KELEMBABAN, PENCAHAYAAN DAN KEPADATAN HUNIAN DENGAN KEJADIAN TB PARU DI INDONESIA (2015 – 2020) - Kencana, Yulfa Tiara (VISIKES, 2024)
Introduction: Tuberculosis is one of the diseases with a high mortality rate and can be a comorbidity of various other diseases, such as obstructive pulmonary disease, HIV/AIDS, and so on. In Indonesia, the number of tuberculosis cases continued to increase from 2016 to 2018. The aim of this research is to analyze the risk factors of humidity, lighting, and residential density on the incidence of Pulmonary TB. Method: This research employed JASP 0.16.4 software. Data sources were collected from the Directory of Open Access Journals (DOAJ), PubMed, the National Library, Digital Reference Center (GARUDA), and Google Scholar. After sorting based on inclusion-exclusion criteria, 15 research articles were selected. The results of the secondary data analysis using the meta-analysis method revealed that the ventilation variable had a 1.716 times higher risk, humidity had a 1.786 times higher risk, lighting had a 3.064 times higher risk, and residential density had a 1.684 times higher risk of causing Pulmonary TB. The conclusion drawn from the results of the meta-analysis is that the lighting variable presents the highest level of risk for the incidence of Pulmonary TB.